Foam-gelcasting preparation of high-strength self-reinforced porous mullite ceramics. Issue 13 (October 2017) - Deng, Xiangong; Ran, Songlin; Han, Lei; Zhang, Haijun; Ge, Shengtao; Zhang, Shaowei
Abstract: High-strength self-reinforced porous mullite ceramics were prepared via foam-gelcasting using mullite powder as a main raw material, AlF3 ·3H2 O (0–8 wt%) as an additive, Isobam-104 as a dispersing and gelling agent, sodium carboxymethyl cellulose as a foam stabilizing agent, and triethanolamine lauryl sulfate as a foaming agent. The effects of AlF3 ·3H2 O content on rheological and gelling behaviors of the slurries, and porosity and mechanical properties of self-reinforced porous mullite samples were examined. Addition of AlF3 ·3H2 O promoted the in-situ formation of elongated mullite in the fired porous samples, which improved considerably their mechanical properties. Compressive strength and flexural strength of 67.0% porous mullite ceramics prepared with addition of 6 wt% AlF3 ·3H2 O was as high as 41.3 and 13.9 MPa, respectively. Its hot modulus rupture (HMOR) increased initially with the testing temperature, and peaked (with a maximum value of 16.6 MPa) at 800 °C above which it started to decrease with the testing temperature. Nevertheless, it was still retained as high as 6.7 and 2.8 MPa at 1200 and 1400 °C, respectively.